TEACHERS’ USE OF CODE SWITCHING IN EFL CLASSROOM AND ITS FUNCTIONS - Puspawati, Indah (Journal of Foreign Language Teaching and Learning, 2018)
The debate about the use of L1 (first language) in EFL (English as a Foreign Language) classes has been around since the teaching as a foreign language itself. The arguments that support the use of L1 use in EFL classes claimed that L1 can be a great tool for students for L2 (English) acquisition and learning. This claims lead to the EFL teachers? use of code switching (CS) in the classroom. This research aims at investigating the teachers? belief about code switching and its function in EFL classroom. Three experienced teachers of English Language Education Department in a private university participated in this study. The study used observation and interview as the data collection methods. The observation was done through video recording on class sessions, and the interview will be done to confirm teachers? use of CS based on the recording. The result reveals that the teachers have made informed decision on their teaching practice, especially on the use of CS as a teaching method to facilitate students? learning. The teachers mostly used inter-sentential switching in CS. The reasons for using CS in the classroom were to help students learn, to facilitate students with low level of L2 proficiency and to teach efficiently. The functions of teachers? CS were to construct and transmit knowledge, to manage the class, and to build interpersonal relation with the students. This study indicated that teachers in this research were aware of the use of CS in teaching and learning L2 to facilitate learning.